2021
DOI: 10.1002/jcop.22775
|View full text |Cite
|
Sign up to set email alerts
|

The potential of psychological connectedness: Mitigating the impacts of COVID‐19 through sense of community and community resilience

Abstract: The purpose of this study was to identify patterns of relationships connecting sense of community (SOC) and community resilience with psychological wellbeing, via the mediation of coronavirus disease 2019 (COVID‐19) impacts on life domains. Survey data were collected from an international sample of adults (n = 824) during the COVID‐19 outbreak (June–September 2020). Using a structural equation model, we tested a mediation model to identify the associations between SOC and community resilience with the perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 82 publications
1
18
0
1
Order By: Relevance
“…However, on the other hand it may also be the case for citizens to trust their community's ability to overcome challenging circumstances at large and get the best out of them both in terms of risks reduction and individual and community enhancement. In either case, it seems like citizens sharing this representation of their community may assume that the latter will take care of itself and of its members throughout the emergency; consistently, they may rely on this significant group to get through it (Mannarini et al, 2021 ) – hence showing lower levels of attention to what is happening and to its implications both as risks and opportunities for themselves. Altogether, these results are consistent with previous studies showing that community collective resilience can act as a buffer against the negative impact of adverse events (Patel et al, 2017 ), yet they add that such representation may also associate with community members thinking less about their own experience of coping and adaptation, henceforth acknowledging fewer space and opportunities for nurturing self‐enhancement too.…”
Section: Discussionmentioning
confidence: 99%
“…However, on the other hand it may also be the case for citizens to trust their community's ability to overcome challenging circumstances at large and get the best out of them both in terms of risks reduction and individual and community enhancement. In either case, it seems like citizens sharing this representation of their community may assume that the latter will take care of itself and of its members throughout the emergency; consistently, they may rely on this significant group to get through it (Mannarini et al, 2021 ) – hence showing lower levels of attention to what is happening and to its implications both as risks and opportunities for themselves. Altogether, these results are consistent with previous studies showing that community collective resilience can act as a buffer against the negative impact of adverse events (Patel et al, 2017 ), yet they add that such representation may also associate with community members thinking less about their own experience of coping and adaptation, henceforth acknowledging fewer space and opportunities for nurturing self‐enhancement too.…”
Section: Discussionmentioning
confidence: 99%
“…The feeling to belong and to be bonded to a cohesive community—characterized by reciprocal attention to everyone's needs and opportunities for reciprocal support—represents a protective factor supporting individuals' adaptation to new life circumstances, well‐being, and efficacy I the face of disruptive events, as showed by recent studies about COVID‐19 pandemic (Gatti & Procentese, 2021 ; Gattino et al, 2021 ; Guidetti & Albanesi, 2021 ; Mannarini et al, 2021 ; Procentese et al, 2020 , 2022 ; Tzankova et al, 2022 ). Indeed, the bond to one's community of belonging “provides individuals with a sense of meaning and continuity, belonging and safety, affirmation, and mattering” (Procentese et al, 2020 , p. 3); it can help them thinking up individual and collective strategies to face challenges and stressful circumstances, broad workloads, and daily needs (Keyes, 2005 ; Scotto di Luzio et al, 2014 ), fostering a more proactive attitude toward the needed changes (Corzine et al, 2017 ; Drzensky et al, 2012 ).…”
Section: Sense Of Community As a Protective Factormentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses on mental health problems seem to point to high depression rates (assessed in different ways) in the general population, ranging from 24 27 to 33.7% 28 . In Italy, different studies on mental health and clinical symptoms have been conducted during the pandemic 11 , 25 , 32 37 , while very few focused on the WB status of citizens 11 , 25 , 36 , 38 . These studies found that COVID-19 significantly impacted WB of Italian citizens 36 , 38 and that WB status was influenced by a variety of different individual and community factors, including social support, psychological flexibility, education levels, family functioning, inability to obtain all basic supplies, mindfulness, living with friends/roommates, gender, age, socioeconomic status, occupational status, coping efficacy, trust in the institutional response, and socioeconomic status 11 , 36 .…”
Section: Discussionmentioning
confidence: 99%